Social Media Usage and its Impact on the Emotional Competencies of Undergraduate Psychology Students - Masih, Sanya Raj; Tripathi, Kaushalendra Mani (Information Research Communications, 2024)
The growing prevalence of social media has raised concerns about its impact on emotional competence, particularly among undergraduate psychology students who are developing essential emotional skills. This study examines the relationship between social media usage and emotional competence in this population. A sample of 192 undergraduate psychology students participated in this correlational study. Social media engagement was assessed using Bergen’s Social Media Addiction Scale (BSMAS), while the Emotional Competence Scale measured various emotional abilities. Pearson’s correlation analysis explored associations between these variables. Results indicate a weak to moderate negative correlation between social media usage and emotional competence. Increased social media engagement was linked to reduced depth of feeling, impaired emotional expression and regulation, lower ability to function with emotions, and difficulty coping with problem emotions. However, no significant relationship was observed between social media usage and the enhancement of positive relationships. These findings suggest that excessive social media engagement may hinder emotional processing and regulation. Given the implications for psychology students, interventions promoting mindful digital use and emotional self-regulation are recommended. Future research should explore moderating factors such as personality traits, gender, and content type to better understand this relationship and inform targeted interventions.
Keywords: Social media usage; Emotional competence; Psychology students; Correlation; Undergraduates